32. Influenza Vaccination Prevalence Among Adults with and without HIV by Race, Age, and Sex. (31st December 2020) - Levine-Hall, Tory; Hood, Nicole; Alexeeff, Stacey; Anderson, Alexandra; Hojilla, J Carlo; Horberg, Michael A; Horberg, Michael A; Lam, Jennifer; Satre, Derek; Silverberg, Michael
Abstract: Background: People with HIV (PWH) may be more likely than people without HIV (HIV-) to receive influenza vaccinations. However, it is unknown if there are demographic differences in vaccination rates and whether this varies by HIV status. Methods: We identified all adult PWH (≥18 years) and 20:1 race-, age- and sex-matched HIV- adults enrolled in Kaiser Permanente Northern California between 2013 - 2017. We evaluated prevalence of influenza vaccinations during the 2013 – 2016 flu seasons (September 1 to March 31). We used Poisson regression models with repeated measures (subjects contributed to multiple flu seasons) to estimate the relative risk [RR] of influenza vaccinations by race, age, and sex within HIV status strata. Multivariable models included terms for HIV status, race, age, sex, unhealthy alcohol use, smoking status, calendar year, alcohol use disorder, census-based education/income, depression, insurance type, and outpatient visits, and interaction terms for HIV*race, HIV*age group, and HIV*sex. Results: The study sample included 7, 422 PWH and 152, 305 HIV-. 90% of PWH and 91% of HIV- were men; mean age at baseline was 49.4 (PWH) and 50.6 (HIV-) years; and 45% of PWH and 44% of HIV- were non-White. In adjusted models, PWH were more likely to receive the influenza vaccine compared with HIV- (RR 1.51; 95% CI 1.50–1.54). Among HIV-, Blacks were less likely to receive the vaccine compared with Whites (RR 0.77; 0.76–0.78); this effect was attenuated in PWH (RR 0.88; 0.84–0.92) (Figure, panel a). Among HIV-, older age groups were more likely to receive the vaccine compared with the 18 – 29 age group, with attenuated RRs among PWH (Figure, panel b). Among HIV-, females were more likely to receive the vaccine compared to males (RR 1.11; 1.09–1.13) while among PWH, females were less likely compared to males (RR 0.94; 0.89–1.00; p=0.04) (Figure, panel c). Adjusted relative risk of influenza vaccination by race, age, and sex Conclusion: PWH were more likely to be vaccinated against influenza than HIV-. In both PWH and HIV-, Blacks and younger age groups were less likely to be vaccinated, although these associations were attenuated in PWH. The effect of sex varied by HIV status with increased vaccination rates for female HIV- but reduced rates for female PWH. Targeted efforts are needed to continue to close the gap in demographic disparities regarding influenza vaccination rates among PWH. Disclosures: Michael Silverberg, PhD, MPH, Gilead Sciences, Inc. (Grant/Research Support)